Flame-retardant hydrophobic self-cleaning coating as well as preparation method and application of cotton fabric containing coating
By forming a two-layer coating structure on cotton fabric, using PEI, PEPA and PDMS materials, combined with alkaline liquid treatment and finishing liquid impregnation steps, the problem of the existing flame retardant coating being reduced after high temperature or multiple cleanings is solved, and efficient flame retardant performance, hydrophobicity and washing resistance are achieved.
Patent Information
- Application Number
- CN202411837357.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-04-15
AI Technical Summary
The flame retardant coatings have significantly reduced flame retardant effects after high temperatures or multiple cleanings, and there are often contradictions in hydrophobicity and durability, making it difficult to maintain high performance after multiple washings.
A two-layer coating structure is adopted, wherein the first layer is formed of a mixed solution of polyethyleneimine (PEI) and pentaerythritol phosphate (PEPA), and the second layer is formed by curing and drying of polydimethylsiloxane solution (PDMS), combining the alkali treatment and finishing impregnation steps to enhance fiber reactivity and coating adhesion.
The flame retardant properties and wash resistance of cotton fabrics are significantly improved, with water contact angles not less than 148°, the limiting oxygen index (LOI) value increased from 18.0% to 28.8%, and the LOI value remained no less than 24% after 40 washes, proving the long-lasting and durability of the coating.
Smart Images

Figure CN119824693A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of functional fabric preparation, and in particular relates to a flame-retardant, hydrophobic, self-cleaning coating, and a preparation method and application of cotton fabric containing the coating. Background Art
[0002] As people's requirements for environmental protection and safety continue to increase, the demand for flame retardant and hydrophobic functional textiles is gradually increasing. Cotton fabric, as a widely used natural textile material, has good air permeability and comfort, but its flammable and hygroscopic properties limit its application in some special fields (such as fireproof clothing, building materials, automotive interiors, etc.). Therefore, the development of coated cotton fabrics with high flame retardancy, excellent hydrophobicity and good durability has become a hot topic in the current research on the functionalization of textiles.
[0003] At present, the common flame retardant coating technologies on the market mainly include chemical treatment and coating. The chemical treatment method improves the flame retardant properties of cotton fabrics by introducing flame retardants into them. However, such flame retardants may release toxic gases, and their effects usually decrease significantly after multiple washings, and there are problems of environmental pollution and poor durability. The coating method achieves a flame retardant effect by coating a layer of flame retardant coating on the surface of cotton fabrics. This method can not only effectively improve the flame retardant properties, but also improve the wear resistance, heat resistance and water resistance of cotton fabrics to a certain extent.
[0004] However, existing coating technologies still face some challenges. First, most existing flame-retardant coatings can only provide limited flame-retardant protection, and the flame-retardant effect gradually decreases at high temperatures or after multiple washings. Second, there is often a certain contradiction between the hydrophobicity and durability of coated cotton fabrics, and the coating often loses its effect as it wears out during use. Therefore, there is an urgent need for a new type of coating material that can maintain excellent flame-retardant properties while having efficient hydrophobicity, good durability, and can maintain high performance after multiple washings. Summary of the invention
[0005] The present invention aims to solve the problems existing in the above-mentioned prior art and provides a flame retardant, hydrophobic and self-cleaning coating, and a preparation method and application of cotton fabric containing the coating.
[0006] One of the purposes of the present invention is to provide a flame retardant, hydrophobic and self-cleaning coating, which is formed on the surface of a protected material in two layers, wherein the first layer is formed by curing and drying a mixed solution of polyethyleneimine (PEI) and pentaerythritol phosphate (PEPA), and the second layer is formed by curing and drying a polydimethylsiloxane solution (PDMS) on the first layer.
[0007] Furthermore, in the mixed solution for forming the first coating layer, the content of pentaerythritol phosphate is 10-15%, preferably 12.5wt%; and the content of polyethyleneimine is 3-5wt%, preferably 4wt%.
[0008] Furthermore, the polyethyleneimine is linear PEI with a molecular weight of 500-1000, preferably 600, and its moderate molecular weight helps to improve the adhesion to the surface of the substrate, thereby enhancing the uniformity and stability of the coating.
[0009] Furthermore, the mass concentration of the polydimethylsiloxane solution is 5-10%.
[0010] Furthermore, the protected material is cotton fabric, polyester fiber, wool or other natural fibers, etc., preferably cotton fabric.
[0011] The second object of the present invention is to provide a method for preparing a cotton fabric containing the flame retardant and hydrophobic self-cleaning coating, comprising the following steps:
[0012] S1: The cotton fabric is immersed in an alkali solution and then taken out, washed with deionized water until neutral and dried to obtain a mercerized cotton fabric;
[0013] S2: immersing the mercerized cotton fabric in a finishing solution, wherein the finishing solution comprises polyethyleneimine (PEI) and pentaerythritol phosphate (PEPA), and after the immersion, taking out the treated cotton fabric and curing and drying it to obtain a cotton fabric with a first layer of coating;
[0014] S3: The flame-retardant treated cotton fabric is immersed in a polydimethylsiloxane solution (PDMS) solution, taken out after immersion, and dried to form a uniform super-hydrophobic coating, thereby achieving super-hydrophobicity and self-cleaning properties of the cotton fabric.
[0015] Furthermore, the alkali solution in step S1 is a NaOH solution with a mass concentration of 1%. The cotton fabric is treated in sodium hydroxide at 90-100° C. for 1 hour.
[0016] Furthermore, the finishing liquid in step S2 is prepared by dissolving pentaerythritol phosphate, polyethyleneimine and dicyandiamide in water, wherein the mass concentration of dicyandiamide is 5%.
[0017] Furthermore, the immersion in step S2 is carried out by stirring in a water bath at 70° C. for 30-60 minutes.
[0018] Furthermore, the curing temperature in step S2 is 110-120° C., the curing time is 30-40 min, and the drying temperature is 130-140° C., the drying time is 5-6 min.
[0019] Furthermore, in the PDMS solution described in step S3, the mass ratio of solvent:PDMS:auxiliary agent is 100:10:1; the solvent is ethanol, and the auxiliary agent is Sylgard 185 (PtCatalyst, DBTDL and DCP).
[0020] Furthermore, the immersion in step S3 is carried out by stirring at room temperature for 8-10 minutes; the drying temperature is 60-70° C. and the drying time is 2-3 hours.
[0021] The third object of the present invention is to provide a cotton fabric containing a flame retardant and hydrophobic self-cleaning coating obtained by the above preparation method.
[0022] Furthermore, the water contact angle of the cotton fabric surface having the two layers of coating is not less than 148°.
[0023] Furthermore, the limiting oxygen index LOI value of the cotton fabric with two layers of coating is still maintained at no less than 24% after 40 washing cycles.
[0024] The cotton fabric containing the flame-retardant and hydrophobic self-cleaning coating prepared by the invention can be used in the fields of household, medical treatment and fire fighting.
[0025] The present invention has the following beneficial effects:
[0026] The present invention not only endows the cotton fabric with excellent superhydrophobic properties, but also significantly enhances its flame retardant properties and washability. The treated cotton fabric shows a significant transition from hydrophilicity to superhydrophobicity, with an initial water contact angle of 148°, and its limiting oxygen index (LOI) is increased from 18.0% of the control cotton fabric to 28.8%, indicating that the flame retardant properties are significantly improved. After 40 washing cycles, the water contact angle remains at 125.1°, and the LOI value is stabilized at about 24%, showing excellent washability and long-lasting performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a schematic diagram of the preparation process of the super hydrophobic flame retardant cotton fabric of the present invention.
[0028] Figure 2 SEM images and water contact angles of untreated cotton fabric and various treated cotton fabric samples: (a1-a2) control cotton fabric (Contrl-Cotton), (b1-b2) cotton fabric-PDMS (Cotton-PDMS), (c1-c2) cotton fabric-PEI / PEPA (Cotton-PEI / PEPA), (d1-d2) cotton fabric-PEI / PEPA@PDMS (Cotton-PEI / PEPA@PDMS).
[0029] Figure 3EDS spectrum and elemental mapping of cotton fabric Cotton-PEI / PEPA@PDMS (a), and FTIR spectrum comparison of control cotton fabric and Cotton-PEI / PEPA@PDMS (b).
[0030] Figure 4 Digital images of control cotton (Contrl-Cotton), cotton-PDMS, cotton-PEI / PEPA, and cotton-PEI / PEPA@PDMS samples during the vertical burning test.
[0031] Figure 5 50kW / m 2 Digital images of control cotton fabric (a), cotton fabric-PDMS (b), cotton fabric-PEI / PEPA (c), and cotton fabric-PEI / PEPA@PDMS (d) after cone calorimetry test (CCT).
[0032] Figure 6 Total heat release (THR) (a), peak heat release rate (HRR) (b), total smoke release (TSP) (c) and smoke generation rate (SPR) (d) curves of cotton fabric samples, characterized by cone calorimeter (CONE).
[0033] Figure 7 TG (a) and DTG (b) curves of cotton fabric samples under nitrogen atmosphere.
[0034] Figure 8 3D TG-FTIR spectra (ab) and FTIR spectra (cd) of cotton fabric and Cotton-PEI / PEPA@PDMS at different temperatures.
[0035] Fig. 9 Scanning electron microscope (SEM) images of control cotton fabric (a1-a2), Cotton-PDMS (b1-b2), control PEI / PEPA (c1-c2) and Cotton-PEI / PEPA@PDMS (d1-d2), and EDS element distribution diagram of control cotton fabric (a3) and Cotton-PEI / PEPA@PDMS (d3) after combustion.
[0036] Fig.10 EDS element distribution diagram of the surface of the control cotton fabric (a) and Cotton-PEI / PEPA@PDMS (b) after combustion
[0037] Fig.11Hydrophobicity test of control cotton fabric and Cotton-PEI / PEPA@PDMS (a1-a2), self-cleaning performance of control cotton fabric (b1-b3) and Cotton-PEI / PEPA@PDMS (c1-c3), gas permeability images of Cotton-PEI / PEPA@PDMS (d1-d2), water contact angle of Cotton-PEI / PEPA@PDMS after 10, 20, 30 and 40 washing cycles (e), and LOI of Cotton-PEI / PEPA@PDMS after washing cycles (f). DETAILED DESCRIPTION
[0038] The present invention will be further described below in conjunction with the accompanying drawings.
[0039] The invention discloses a coating with self-cleaning and hydrophobic properties. The coating is formed on the surface of a protected material in two layers. The first layer is formed by curing and drying a mixed solution of polyethyleneimine (PEI) and pentaerythritol phosphate (PEPA), and the second layer is formed by curing and drying a polydimethylsiloxane solution (PDMS) on the first layer.
[0040] In the mixed solution for forming the first coating layer, the contents of pentaerythritol phosphate (PEPA) and polyethyleneimine (PEI) are 12.5wt% and 4wt% respectively, and the concentration of the polydimethylsiloxane solution is 5% to 10%.
[0041] Example 1
[0042] The protected material is cotton fabric, and the preparation method for forming a coating on the cotton fabric is as follows:
[0043] S1: The cotton fabric was immersed in sodium hydroxide (NaOH) alkali solution and treated at 90-100°C for 1 hour to remove impurities and enhance fiber reactivity while avoiding cellulose degradation. After treatment, it was rinsed with deionized water to neutral pH. It was then dried at 70°C for 3 hours.
[0044] S2: Mercerized cotton fabric was used as the starting material and soaked in an aqueous solution containing 12.5wt% pentaerythritol phosphate (PEPA), 4wt% polyethyleneimine (PEI) and 5wt% dicyandiamide. The mixture was stirred in a water bath at 70°C for 30 minutes to ensure that the coating was evenly applied to the cotton fabric. The fabric was then pre-cured at 110°C for 30 minutes and then baked at 130°C for 6 minutes. The resulting fabric was labeled Cotton-PEI / PEPA.
[0045] S3: Use Cotton-PEI / PEPA as the substrate to ensure that the surface is clean and free of impurities. Prepare a hydrophobic solution with a mass ratio of solvent: PDMS: Sylgard 185 of 100:10:1, and ethanol as the solvent. Soak the Cotton-PEI / PEPA sample in the hydrophobic solution and stir at room temperature for 8 minutes to ensure uniform mixing and sufficient dispersion. After soaking, lay the fabric flat and place it in a preheated oven for curing until completely dry. The temperature and curing time were optimized according to the curing characteristics of PDMS. The treated fabric was named Cotton-PEI / PEPA@PDMS.
[0046] The water contact angle of the cotton fabric surface is not less than 148°, and the limiting oxygen index LOI value after 40 washing cycles is still maintained at not less than 24%.
[0047] Example 2
[0048] The protected material is cotton fabric, and the preparation method for forming a coating on the cotton fabric is as follows:
[0049] S1: The cotton fabric was immersed in sodium hydroxide (NaOH) alkali solution and treated at 90-100°C for 1 hour to remove impurities and enhance fiber reactivity while avoiding cellulose degradation. After treatment, it was rinsed with deionized water to neutral pH. It was then dried at 70°C for 3 hours.
[0050] S2: Use Cotton-PEI / PEPA as the substrate and ensure that the surface is clean and free of impurities. Prepare a hydrophobic solution with a ratio of 100:10:1 solvent: PDMS: Sylgard 185, and use ethanol as the solvent. Soak the Cotton-PEI / PEPA sample in the hydrophobic solution and stir at room temperature for 8 minutes to ensure uniform mixing and sufficient dispersion. After soaking, lay the fabric flat and place it in a preheated oven for curing until completely dry. The temperature and curing time were optimized according to the curing characteristics of PDMS. The treated fabric is named Cotton-PDMS.
[0051] Example 3
[0052] The protected material is cotton fabric, and the preparation method for forming a coating on the cotton fabric is as follows:
[0053] S1: The cotton fabric was immersed in sodium hydroxide (NaOH) alkali solution and treated at 90-100°C for 1 hour to remove impurities and enhance fiber reactivity while avoiding cellulose degradation. After treatment, it was rinsed with deionized water to neutral pH. It was then dried at 70°C for 3 hours.
[0054] S2: Mercerized cotton fabric was used as the starting material and soaked in an aqueous solution containing 12.5wt% pentaerythritol phosphate (PEPA), 4wt% polyethyleneimine (PEI) and 5wt% dicyandiamide. The mixture was stirred in a water bath at 70°C for 30 minutes to ensure that the coating was evenly applied to the cotton fabric. The fabric was then pre-cured at 110°C for 30 minutes and then baked at 130°C for 6 minutes. The resulting fabric was labeled Cotton-PEI / PEPA.
[0055] The surface morphology and wettability of the control cotton fabric and Cotton-PEI / PEPA@PDMS were analyzed by scanning electron microscopy (SEM) and water contact angle (WCA) measurements. Figure 2 As shown, the control cotton fabric sample ( Figure 2 a1-a2) show a typical fiber structure with a smooth and neatly arranged surface, showing strong hydrophilicity. After PDMS treatment ( Figure 2 b1-b2), the fiber surface becomes smoother and the water contact angle increases significantly to 125.1°, indicating that the hydrophobicity is enhanced. Samples treated with PEI / PEPA ( Figure 2 c1-c2) The surface is relatively rough and there are particles deposited. Despite the rough surface, the fiber still shows hydrophilicity and water droplets easily adhere to the surface. Cotton-PEI / PEPA@PDMS sample ( Figure 2 d1-d2) shows a hierarchical surface that combines surface roughness with PDMS-induced hydrophobicity to form a superhydrophobic surface with a water contact angle of 148.4°. This clearly demonstrates the improvement in hydrophobicity, which is attributed to the synergistic effect of the rough microstructure and the low surface energy of the PDMS coating.
[0056] EDS spectroscopy and elemental mapping ( Figure 3 a) Clearly demonstrates the elemental composition of Cotton-PEI / PEPA@PDMS, indicating the presence of oxygen (O), carbon (C), nitrogen (N), silicon (Si), and phosphorus (P). The detection of silicon confirms the successful introduction of the PDMS coating, while the presence of phosphorus verifies the addition of PEPA. In addition, the detection of nitrogen further confirms the effective attachment of PEI. The significant changes in the OH and NH peak intensities compared to untreated cotton fabric indicate that the surface chemical structure has been altered, confirming the successful introduction of the PEI coating. The uniform distribution of these elements indicates that PEI, PEPA, and PDMS have been evenly coated on the cotton fabric surface, ensuring the consistency and integrity of the coating. FTIR Spectrum ( Figure 3 b) shows the significant difference in the absorption peak between the control cotton fabric and Cotton-PEI / PEPA@PDMS. Approximately 1100 cm - 1(Si-O-Si) and 1250cm -The characteristic peak at 1 (P=O) confirms the successful introduction of PDMS and PEPA coatings. The significant changes in the OH and NH peak intensities further indicate the changes in the surface chemical structure after treatment, verifying the successful introduction of PEI coating. PDMS effectively reduces the surface energy by forming a stable Si-O-Si network and significantly enhances the hydrophobicity. At the same time, the introduction of PEPA imparts excellent flame retardant properties because phosphorus helps to form a char layer at high temperatures, thereby inhibiting combustion. The synergistic effect of PDMS and PEPA not only makes the material superhydrophobic, but also significantly improves its fire resistance, highlighting the advantages of PEI / PEPA@PDMS coating in the functional modification of cotton fabrics, especially in terms of simultaneously improving hydrophobicity and flame retardancy.
[0057] The flammability of control cotton fabric (ContrlCotton), cotton fabric-PDMS, cotton fabric-PEI / PEPA, and cotton fabric-PEI / PEPA@PDMS was evaluated by limiting oxygen index (LOI) and vertical burning test (VFT). The results are summarized in Tables 1 and Figure 4 The LOI value of the control cotton fabric was 18.0±0.3%, indicating its high flammability. The LOI value of cotton fabric-PDMS increased slightly to 20.6±0.2%, indicating that the flame retardant properties were improved, but the effect was limited. However, the LOI value of cotton fabric-PEI / PEPA increased significantly to 26.4±0.4%, while the LOI value of cotton fabric-PEI / PEPA@PDMS was further improved to 28.8±0.3%, showing the synergistic effect of PEI and PEPA in enhancing the flame retardant properties. In the VFT test, the afterflame time of the control cotton fabric was 30±8 seconds, the afterglow time was 73±6 seconds, and the damage length was 30 cm. In contrast, the cotton fabrics coated with PEI / PEPA and PEI / PEPA@PDMS both showed excellent self-extinguishing properties, without afterflame or afterglow, and the damage lengths were shortened to 4.7±0.5 cm and 4.3±0.3 cm, respectively. These results indicate that the PEI / PEPA@PDMS coating significantly improves the flame retardant properties of cotton fabrics, as manifested by higher LOI values, shorter afterflame and afterglow times, and significantly reduced damage length.
[0058] Table 1. LOI and VFT data
[0059]
[0060] Figure 5 The digital images in the figure show the control cotton fabric (Contrl-Cotton), cotton fabric-PDMS, cotton fabric-PEI / PEPA and cotton fabric-PEI / PEPA@PDMS at 50 kW / m 2Results under the Cone Calorimeter Test (CCT). The control cotton fabric burned almost completely, leaving a small amount of ash ( Figure 5 a). In contrast, although cotton fabric-PDMS retains some structure, the surface is obviously damaged ( Figure 5 b). Cotton fabric-PEI / PEPA showed good structural integrity, and the carbon layer was relatively intact ( Figure 5 c). It is worth noting that cotton fabric-PEI / PEPA@PDMS formed a more uniform and stable grid-like residue after combustion, and the carbonization effect was the most significant ( Figure 5 d). These results indicate that the synergistic effect between PEI / PEPA and PDMS significantly enhances the thermal stability and flame retardancy of cotton fabrics, leading to the formation of a stronger char layer and improved structural integrity under high heat flux conditions.
[0061] Table 2. Combustion performance data tested by cone calorimeter
[0062]
[0063] The combustion performance of different cotton fabric samples was comprehensively analyzed by cone calorimeter (CONE) test, as shown in Table 2 and Figure 6 The data show the changes in heat release rate (HRR), total heat release (THR), total smoke generation (TSP) and smoke generation rate (SPR) over time. Compared with the control cotton fabric, the HRR of the cotton fabric-PEI / PEPA@PDMS sample is significantly reduced, with a peak HRR of only 47 kW / m 2 , while the HRR of the control cotton fabric is 73 kW / m 2 , indicating that the burning intensity is greatly reduced. In addition, the THR of cotton fabric-PEI / PEPA@PDMS is 1.2 MJ / m 2 , significantly lower than the 2.0 MJ / m 2 , indicating that the coating system can effectively inhibit the energy release during combustion. Compared with the untreated control cotton fabric, the peak HRR of cotton fabric-PEI / PEPA@PDMS was reduced by 35.6% and the THR was reduced by 40.0%, showing an excellent condensed phase flame retardant effect. This reduction in flame propagation provides firefighters with more rescue time. Although the TSP of the cotton fabric-PEI / PEPA@PDMS sample is 0.35m 2 / kg, higher than the 0.06m of the control cotton fabric 2 / kg, but the increased smoke generation was mainly attributed to incomplete combustion. In terms of fire performance index (FPI) and fire growth index (FGI), the FPI of cotton fabric-PEI / PEPA@PDMS sample was 0.87m 2·s / kW, significantly higher than the FPI of the control cotton fabric 0.11m 2 ·s / kW, indicating that its fire protection performance has been improved. The FGI of the cotton fabric-PEI / PEPA@PDMS sample is 1.15kW / m 2 ·s, much lower than the 9.13kW / m of the control cotton fabric 2 ·s, indicating that the coating system effectively reduces the heat release rate and flame spread, significantly reduces the fire risk, and enhances safety and rescue potential.
[0064] Table 3. Thermogravimetric analysis and differential thermogravimetric analysis data
[0065]
[0066] As shown in Table 3 and Figure 7 As shown, the thermal stability of cotton fabrics was evaluated by thermogravimetric analysis (TGA) and differential thermogravimetric analysis (DTG) under nitrogen atmosphere. Compared with the control cotton fabric, the initial decomposition temperature (T5%) and maximum decomposition temperature (Tmax) of Cotton-PEI / PEPA@PDMS fabrics were lower. This is due to the early degradation of PEI / PEPA@PDMS coating at high temperature, accompanied by the release of ammonia (NH3) and water (H2O), forming phosphoric acid and polyphosphoric acid. These acids catalyze the carbonization of cellulose, promote the formation of carbon layer, and significantly reduce the flammability of the material.
[0067] In addition, at 800°C, the carbon residue of the coated fabrics was significantly higher than that of the control cotton fabric. The residual masses of Cotton-PDMS, Cotton-PEI / PEPA, and Cotton-PEI / PEPA@PDMS were 27.5%, 37.8%, and 41.7%, respectively, while the residual mass of the control cotton fabric was only 7.5%. The significant increase in the amount of carbonization highlights the superior flame retardant properties of the coated fabrics. Figure 5 As shown in Figure 2, the char layer of Cotton-PEI / PEPA@PDMS after combustion is dense and structurally intact, which effectively acts as an oxygen barrier, inhibits combustion, and maintains the structural integrity of the fabric.
[0068] In order to analyze the flame retardant mechanism of the system, Figure 8 The 3D TG-FTIR spectra (ab) and FTIR spectra (cd) of the control cotton fabric and Cotton-PEI / PEPA@PDMS at different temperatures are shown. Figure 8ab), the control cotton fabric mainly produces typical thermal degradation products such as CO2, CH, OH and COC. This shows that cellulose decomposes rapidly at high temperatures, releasing a large amount of combustible gases and lacks sufficient anti-burning protection. In contrast, Cotton-PEI / PEPA@PDMS shows significantly different spectral characteristics. In addition to the common CO2 and CH peaks, additional peaks of NH, POP and Si-O-Si appear. The appearance of NH and POP peaks indicates that nitrogen and phosphorus-containing groups are released during pyrolysis, which promotes the formation of a carbon layer and reduces the release of combustible gases. The Si-O-Si peak shows that PDMS forms a stable silicon oxygen layer at high temperatures, further enhancing the flame retardant properties of the material.
[0069] FTIR spectra at different temperatures ( Figure 8 cd) further verified this mechanism. With the increase of temperature, the CO2 and CH absorption peaks of the control cotton fabric became more obvious, especially above 500°C, indicating that cellulose degradation accelerated and released combustible gases such as ethers, promoting rapid combustion. In contrast, Cotton-PEI / PEPA@PDMS showed the development of POP and Si-O-Si peaks at similar temperatures, indicating that the phosphorus groups formed a carbon layer, while the silicon-oxygen network acted as a barrier, effectively reducing the release of combustible gases and inhibiting the transfer of heat and oxygen. In addition, the appearance of the NH absorption peak confirmed that nitrogen-containing compounds further suppressed the generation of combustible gases at high temperatures and slowed down the combustion process. Overall, Cotton-PEI / PEPA@PDMS exhibited enhanced thermal stability and flame retardant properties through a synergistic mechanism.
[0070] The flame retardant mechanism of Cotton-PEI / PEPA@PDMS coating can be summarized as follows: Fig. 9 and Fig.10 The SEM images and EDS element distribution results of control cotton fabric, Cotton-PDMS, Contrl-PEI / PEPA and Cotton-PEI / PEPA@PDMS after combustion are shown, revealing the effects of different treatments on flame retardancy. Fig. 9 As shown in a1-a2, the control cotton fabric showed serious fiber structure degradation after burning, and the carbon layer appeared as white ash. EDS analysis ( Fig.10 This observation was further confirmed by the presence of only small amounts of residual carbon and oxygen, indicating that the material was unable to form an effective char layer during combustion. Fig. 9 In b1-b2, Cotton-PDMS forms some silicon oxide after combustion, which provides some protection, but its flame retardant effect is limited because the fiber still shows significant damage. Fig. 9As shown in c1-c2, the Contrl-PEI / PEPA cotton fabric formed a more complete carbon layer after combustion, and the fiber structure was well preserved. This indicates that the synergistic effect of PEI and PEPA promoted the formation of a stable carbon layer and inhibited further decomposition. Fig. 9 As shown in d1-d2, Cotton-PEI / PEPA@PDMS formed a denser and more complete carbon layer after combustion, and the surface damage was significantly reduced. Fig.10 EDS analysis in b shows that the carbon content of Cotton-PEI / PEPA@PDMS increased significantly after combustion, and a large amount of phosphorus (P) and silicon (Si) elements remained on the surface. The silicate residues acted as an insulating layer, effectively slowing down the volatilization of decomposition products and protecting the cotton fabric surface from external heat flow. Phosphorus contributes to the formation of a flame-retardant carbon layer, while silicon significantly enhances the thermal stability and barrier properties of the material by forming silicon dioxide. After applying the PEI / PEPA@PDMS coating, a denser and more stable carbon layer was formed on the cotton fabric surface. The synergistic effect of PEI and PEPA significantly improved the flame retardancy, while the addition of PDMS not only enhanced the hydrophobicity but also contributed to the thermal stability and barrier effect at high temperatures by forming silicon oxides. These combined effects promoted carbonization in a flame environment and effectively inhibited the propagation of heat and flammable products, thereby significantly improving the heat resistance and structural integrity of cotton fabrics.
[0071] like Fig.11 As shown, Fig.11 a1 and Fig.11 a2 shows the hydrophobicity test results of control cotton fabric (Contrl Cotton) and Cotton-PEI / PEPA@PDMS, respectively. Different liquids, such as milk, vinegar, ink, coffee, mud, water, tea and ammonia, were dropped onto the untreated control cotton fabric. It can be clearly seen that most of the liquids spread and were absorbed on the fabric, especially ink and mud, which penetrated deeply and left obvious stains, indicating that the cotton fabric is hydrophilic. In contrast, the cotton fabric coated with PEI / PEPA@PDMS exhibited excellent hydrophobic properties. The liquid formed spherical water droplets on its surface and did not penetrate into the fabric, confirming that the coating treatment significantly enhanced the hydrophobicity of the cotton fabric. Fig.11 A control cotton fabric ( Fig.11 b1-b3) and Cotton-PEI / PEPA@PDMS ( Fig.11 c1-c3) self-cleaning performance. Fig.11 In b1-b3, red chalk dust was applied to the surface of the control cotton fabric, and even after the application of water (as shown in b2 and b3), the contaminant remained on the surface of the fabric, indicating that its self-cleaning ability was poor. Fig.11c1-c3 show the self-cleaning performance of Cotton-PEI / PEPA@PDMS. Fig.11 After adding water to c2, the pollutants are easily washed away, such as Fig.11 As shown in c3, the fabric surface becomes clean. This indicates that the coating significantly improves the self-cleaning properties of Cotton-PEI / PEPA@PDMS fabric, which is attributed to its superhydrophobic coating. The Cotton-PEI / PEPA@PDMS fabric was tightly fixed at the opening of the beaker using a rubber band to prevent air leakage. Hydrochloric acid (HCl) solution was placed in the beaker, and methyl orange solution was dripped on the fabric surface. Fig.11 As shown in d1-d2, the methyl orange solution turns red, indicating that hydrochloric acid gas diffuses through the fabric and contacts the methyl orange. This color change confirms that the Cotton-PEI / PEPA@PDMS fabric is breathable and capable of gas exchange. Fig.11 e shows the change in water contact angle (WCA) of the Cotton-PEI / PEPA@PDMS sample after 10, 20, 30, and 40 washes. The WCA gradually decreases with the increase in the number of washing cycles. The WCA was 148° when the initial sample was not washed. After 10 washes, the WCA dropped to 141.9°, and after 20 washes, the WCA further dropped to 138.9°. After 30 and 40 washes, the WCA dropped to 133.5° and 125.1°, respectively. Although the WCA decreased over time, it remained at 125.1° even after 40 washes, indicating that the coating can still maintain its hydrophobic properties after multiple washes. Fig.11 f shows the limiting oxygen index (LOI) values of Cotton-PEI / PEPA@PDMS after different washing cycles, demonstrating the effect of repeated washing on the flame retardant properties of the coated fabric. Initially, at 0 washing cycles, the LOI value was approximately 28%, indicating strong flame retardancy. However, with increasing washing cycles, the LOI value gradually decreased, reflecting the weakening of the flame retardant effect due to the wear and possible degradation of the coating. After 40 washing cycles, the LOI value dropped to approximately 24%, indicating a significant decrease in flame retardancy, but not yet a complete loss. This trend emphasizes that although the Cotton-PEI / PEPA@PDMS coating provides enhanced flame retardant properties, its effect weakens with increasing washing cycles, which is an important factor for the durability of this material in practical applications.
[0072] The above description is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements without departing from the principle of the present invention, and these improvements should also be regarded as within the protection scope of the present invention.
Claims
1. A flame retardant, hydrophobic, self-cleaning coating, characterized in that: The coating is formed on the surface of the protected material in two layers. The first layer is formed by curing and drying a mixed solution of polyethyleneimine and pentaerythritol phosphate, and the second layer is formed by curing and drying a polydimethylsiloxane solution on the first layer.
2. The flame retardant and hydrophobic self-cleaning coating according to claim 1, characterized in that: The polyethyleneimine is linear PEI with a molecular weight of 500-1000.
3. The flame retardant and hydrophobic self-cleaning coating according to claim 1, characterized in that: The protected material is cotton fabric, polyester fabric, or wool fabric.
4. A method for preparing a cotton fabric containing the flame retardant, hydrophobic and self-cleaning coating according to any one of claims 1 to 3, characterized in that: The steps include: S1: The cotton fabric is immersed in an alkali solution and then taken out, washed with deionized water until neutral and dried to obtain a mercerized cotton fabric; S2: immersing the mercerized cotton fabric in a finishing solution, wherein the finishing solution comprises polyethyleneimine and pentaerythritol phosphate, and after the immersion, taking out the treated cotton fabric and performing curing and drying to obtain a cotton fabric having a first layer of coating; S3: Immersing the flame-retardant treated cotton fabric in a polydimethylsiloxane solution, taking it out after immersion, and drying it to form a uniform super-hydrophobic coating, thereby achieving super-hydrophobicity and self-cleaning properties of the cotton fabric.
5. The method for preparing a cotton fabric containing a flame retardant and hydrophobic self-cleaning coating according to claim 4, characterized in that: The alkali solution in step S1 is a NaOH solution with a mass concentration of 1%; and / or, the cotton fabric is treated in sodium hydroxide at 90-100° C. for 1 hour.
6. The method for preparing the flame-retardant, hydrophobic and self-cleaning coated cotton fabric according to claim 4, characterized in that: The finishing liquid described in step S2 is prepared by dissolving pentaerythritol phosphate, polyethyleneimine and dicyandiamide in water; wherein the content of pentaerythritol phosphate is 10-15wt%, the content of polyethyleneimine is 3-5wt%, and the content of dicyandiamide is 5wt%.
7. The method for preparing the flame-retardant, hydrophobic and self-cleaning coated cotton fabric according to claim 4, characterized in that: In step S2, the immersion is carried out by stirring in a water bath at 70°C for 30-60 minutes; the curing temperature is 110-120°C, and the curing time is 30-40 minutes; the drying temperature is 130-140°C, and the drying time is 5-6 minutes.
8. The method for preparing the flame-retardant, hydrophobic and self-cleaning coated cotton fabric according to claim 4, characterized in that: In the polydimethylsiloxane solution described in step S3, the mass ratio of solvent: polydimethylsiloxane: auxiliary agent is 100:10:1; the solvent is ethanol, and the auxiliary agent is Sylgard 185.
9. The method for preparing the flame-retardant, hydrophobic and self-cleaning coated cotton fabric according to claim 4, characterized in that: The immersion in step S3 is carried out by stirring at room temperature for 8-10 minutes; the drying temperature is 60-70° C. and the drying time is 2-3 hours.
10. Cotton fabric containing a flame retardant, hydrophobic and self-cleaning coating prepared by the method according to any one of claims 4 to 9.